Privacy-Preserving Social Media With Unlinkability and Disclosure - Hideaki Miyaji; Po-Chu Hsu; Atsuko Miyaji (IEEE Access, 2023)
Social media ( ${\sf SM}$ ) has become a primary communication tool in the modern world, with an ever-increasing volume of users. Many ${\sf SM}$ users use anonymous nicknames as their public usernames. However, Zhang et al. (2018) were able to demonstrate an attack that can identify users from the contents of their posts. This attack is caused by the fact that two different posts can be guessed to be the same user. Such linking of different posts is called a linkable feature. On the other hand, usually post under an anonymous nickname, but when a post is thrust into the limelight, we may want to claim the post as our own. Unfortunately, however, current SM offers only two options: using an anonymous nickname or publishing under our own name. In other words, the function of disclosure, which is to make some posts public even though they are usually anonymous, has not been realized in existing ${\sf SM}$ . In this paper, we propose a ${\sf SM}$ with unlinkability and disclosure simultaneously, which is achieved by applying a commitment scheme. A commitment scheme consists of commitment and decommitment phases. As for unlinkability, we newly introduce a one-time post name, which is a commitment value of nickname and post. As for disclosure, we use a decommitment phase to one-time post name. We also have demonstrated that our ${\sf SM}$ is practically feasible.